Аналітичний метод визначення часу розгону в комп'ютерному моделюванні динамічної системи "автомобіль-дорога" - Грицук, Ігор; Грицук, Юрій; Савенков, Микита (Видавництво Національного університету «Львівська політехніка», 2009)
The article is devoted to the actual problem of using of information technologies in the motor transport design. Application of analytical and graphic method of time determination of vehicle accelereation and its realization in Microsoft Excel is considered. A calculation complex for the analysis of the system "car-road" is represented in the article.
Keywords: design; information technologies; analysis; vehicle